Five new species of Cymatodera Gray, 1832 (Coleoptera: Cleridae: Tillinae) from Mexico and Central America - Burke, Alan F.; Sole, Catherine L.; Toledo-Hernández, Víctor H.; Scholtz, Clarke H. (Zootaxa, 2017)
Five new species of Cymatodera from Mexico, Guatemala, Honduras, Costa Rica and Panama are described here based on adult male and female specimens: Cymatodera humeralis sp. n; Cymatodera lorenae sp. n.; Cymatodera crassa sp. n.; Cymatodera depressa sp. n; and Cymatodera nigrofasciata sp. n. Male genitalia and other characters of taxonomic value are used for diagnostic purposes.